Model Akuntansi Sederhana Untuk Penyelenggaraan Pembukuan Bagi Peternak Lele Di Kelurahan Ngronggo Kota Kediri - Duwi Riningsih; Lusia Lapir Atamina; Sudjiono Sudjiono (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The aims this activity to train the ability to carry out bookkeeping independently and introduce financial report. The targets in the Community Abdimas activities are the catfish farmer at Ngronngo Kediri City. Submission of material with lecturers from the Faculty of Economics By using the method of delivering presentations and explanations in front of the audience and supported by the provision of material modules that will be used during the learning period. The constraints faced are a lack of knowledge regarding previous bookkeeping records. The benefits gained by participants from the Community Abdi activities include helping to achieve awareness for the catfish farmer to the importance of financial reporting on their business through simple bookkeeping and also indirectly creating good management in improving catering business.